Design optimization of a CFRP–aluminum joint for a bioengineering application. (2019) - Pappas, G. A.; Botsis, J.
Abstract : Lightweight design demands and complexity requirements of modern high-end structures in aerospace, automotive, sports and bioengineering can be successfully covered by a combination of fiber reinforced polymers (FRPs) with metallic components. Conventionally, mechanical locking is favored in integrating multi-material parts, avoiding bonded interfaces. The feasibility of a multi-material carbon FRP–aluminum structural component of a robotic exoskeleton, fabricated in a single step with the FRP directly cured on the aluminum domain, was investigated. To conduct the feasibility analysis, pertinent systematic FE modeling involving cohesive contact was employed to optimize the design, while strength and fracture testing were conducted to define the formed interfaces' resistance. Sandblasting treatment was also investigated and compared with plain surfaces. The results show that the effect of residual stresses due to curing process governs the created joint's durability. To reduce their effect, the local compliance of the multi-material components was altered by introducing a compliant layer along with modification of the aluminum domains' local geometry in a manner that does not compromise the overall structural integrity. The interface stresses of the optimized geometry are a few times lower than the ones estimated for the initial design. The methodology adopted herein delivers some guidelines on treating such problems.